Overclaim Iklan Dan Kinerja Produk: Peran BPKN Dalam Pengawasan Perlindungan Konsumen - Arifin, Antoni Ludfi; Nugroho, Joko (Jurnal Ilmiah METANSI ”Manajemen dan Akuntansi”, 2026)
This study examines the discrepancy between advertising claims (overclaim) and product performance from a consumer protection perspective in the digital economy era. The background of this research lies in the increasing use of aggressive marketing practices that potentially mislead consumers and create a gap between expectations and actual product performance. This study aims to analyze the impact of overclaim on consumer behavior and to examine the role of the National Consumer Protection Agency/Badan Perlindungan Konsumen Nasional (BPKN) in strengthening market supervision. The research employs a qualitative approach using a literature review method with thematic analysis of various academic publications and policy documents. The findings reveal that overclaim and misleading advertising lead to economic losses, declining consumer trust, and market distortion due to information asymmetry. In addition, weak supervision remains a key factor contributing to the persistence of such practices. The study concludes that strengthening the role of BPKN and institutional capacity is crucial to enhancing consumer protection effectiveness. The implications highlight the need for technology-based supervision systems, improved human resource competencies, and stronger inter-agency coordination to develop an adaptive and responsive consumer protection system.